Physical Sequestration of Bacillus anthracis in the Pulmonary Capillaries in Terminal Infection. (14th March 2016) - Jouvion, Gregory; Corre, Jean-Philippe; Khun, Huot; Moya-Nilges, Marie; Roux, Pascal; Latroche, Claire; Tournier, Jean-Nicolas; Huerre, Michel; Chrétien, Fabrice; Goossens, Pierre L.
Abstract: The lung is the terminal target of Bacillus anthracis before death, whatever the route of infection (cutaneous, inhalational, or digestive). During a cutaneous infection in absence of toxins, we observed encapsulated bacteria colonizing the alveolar capillary network, bacteria and hemorrhages in alveolar and bronchiolar spaces, and hypoxic foci in the lung (endothelial cells) and brain (neurons and neuropil). Circulating encapsulated bacteria were as chains of approximately 13 µm in length. Bacteria of such size were immediately trapped within the lung capillary network, but bacteria of shorter length were not. Controlling lung-targeted pathology would be beneficial for anthrax treatment.